Golden Mean and Proportion in Dental Esthetics after Orthodontic Treatments: An In Vivo Study - Patrizia Lucchi; Giulia Fortini; Giorgia Preo; Antonio Gracco; Alberto De Stefani; Giovanni Bruno (MDPI AG, 2022)
Purpose: The definition of the golden ratio was established around the sixth century BC; Levin and Snow developed specific theories applicable in dentistry, which apply the golden proportion rule with the intention of reproducing a perfect smile. This study analyzed the literature and assessed whether these concepts remain valid and applicable in clinical practice, evaluating the theories with a group of patients followed by an experienced orthodontic team. Methods: This study was retrospectively performed on 400 patients (241 females and 159 males) who underwent orthodontic treatments. The analysis was conducted on intraoral frontal photos, both pre-treatment and post-orthodontic treatment, to observe if there was a statistically significant difference in the tooth display according to the golden mean and golden proportion theories. Results: The canine at the end of the orthodontic treatment had a greater visibility than that proposed by Levin and Snow. Conclusions: This study revealed how these theories could be considered in certain respects, but nowadays are not totally valid and applicable to the clinical reality. Snow's theory appears to be more consistent with the clinical findings than Levin's theory.